Efetivação da garantia de defesa no estado constitucional de direito: colisão entre o poder punitivo e garantia de defesa - Alves, Fábio Wellington Ataíde (2008)
The domination of the violence for the Rule of law awakened a tension between the practice of the punitive power and the right to counsel. However, throughout the recent history of the Criminal law, this shock of forces has been determined for the punitive power. In this perspective, the present work intends to submit the guarantee of defense to a critical judgment, in search to conciliate its content to the Constitutional State of Right. For in such a way, it will be necessary to recognize the disequilibrium of the situation, but without considering the superiority of any of these elements. The State in such a way must fulfill the function to punish the culprits as to acquit the innocents. Despite the law is far from obtaining a harmonious speech, it is necessary that the defense guarantee coexists the punitive power as part of an only public interest, which is, to make criminal justice. In such a way, the existence of a sustainable balance between the punitive power and the guarantee of defense depend on the minimum interference of Criminal law and, also, of the judicial position in the concrete case. The present work faces, therefore, the moment of crisis of the Criminal law, consolidated with the advent of a new way of thinking according to the procedural guarantees, that will demand the overcoming of the old concepts. The Constitutional State of Right not only constitutes an efectiveness of the regime of the right to counsel, but in a similar way it searchs to accomplish the right of action and criminal justice as a whole. Knowing that the philosophy of the language raises doubts on the certainty, the truth and the judgement, it is imposed to understand that the defense guarantee is no more about a simple idea, but, in the crooked ways of the communication, we intend to find what the judge s function is when he faces this new reality